Making science work in mental health care - Iris M. Engelhard (European Journal of Psychotraumatology, 2012)
There is increasing attention for embedding research in mental healthcare. This involves a linkage between scientific research and routine practice, where research is fed by questions from practice and scientific insights are implemented better and faster in clinical practice. This paper illustrates bridging the gap, by focusing on eye movement desensitisation and reprocessing (EMDR), and provides arguments why it is relevant to connect research and practice. It also discusses why experimental psychopathology may have a substantial contribution.For the abstract or full text in other languages, please see Supplementary files under Reading Tools online